PEMANFAATAN QUIZIZZ UNTUK PTM PADA MATA PELAJARAN MATEMATIKA - DIAH LESTARI (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
The Covid-19 pandemic has presented challenges, especially in the world of education. Limited face-to-face learning must be carried out in areas that have met the requirements according to the provisions. Teachers must design effective and fun learning in order to achieve optimal learning quality. The purpose of writing this article is to describe the use of Quizizz as a learning medium in 100% Limited PTM in mathematics. The writing of this article uses a literature study/literature study. The required data is collected through text studies from research results published in national online journals and textbooks. Based on the literature study, it shows that Quizizz is an innovative, creative and fun learning media and is effectively used in learning. Quizizz has interesting features so that it can improve the concentration, motivation and learning outcomes of students so that it can be used as an alternative medium for learning mathematics. ABSTRAKMasa pandemi Covid-19 ini memberikan tantangan khususnya dunia pendidikan. Pembelajaran tatap muka terbatas harus dilaksanakan pada daerah yang telah memenuhi syarat sesuai ketentuan. Guru harus mendesain pembelajaran yang efektif dan menyenangkan agar tercapai kualitas pembelajaran yang optimal. Tujuan penulisan artikel ini adalah untuk mendeskripsikan tentang pemanfaatan Quizizz sebagai media pembelajaran dalam PTM Terbatas 100% pada mata pelajaran matematika. Penulisan artikel ini menggunakan studi kepustakaan/studi literatur. Data yang diperlukan dihimpun melalui kajian teks dari hasil penelitian yang dipublikasikan pada jurnal online nasional dan buku teks. Berdasarkan studi literatur menunjukkan bahwa Quizizz merupakan media pembelajaran yang inovatif, kreatif dan menyenangkan serta efektif digunakan dalam pembelajaran matematika. Quizizz memiliki fitur-fitur yang menarik sehingga dapat meningkatkan konsentrasi, motivasi dan hasil belajar peserta didik sehingga dapat dimanfaatkan sebagai alternatif media pembelajaran matematika.